2021
DOI: 10.1371/journal.pone.0251151
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and preventive behaviors regarding COVID-19 in Bangladesh: A nationwide distribution

Abstract: Assessing individuals’ knowledge and preventive behaviors towards the Coronavirus Disease of 2019 (COVID-19) is essential for the related public health surveillance strategies. Although some of the studies were conducted in Bangladesh, none of these studies considered the geographical distribution of knowledge and preventive behaviors towards COVID-19. Therefore, the present nationwide cross-sectional study with 10,067 samples for the first-time aims to assess the knowledge gap by presenting the geographical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 31 publications
4
51
0
2
Order By: Relevance
“…Based on the present findings, it is evident that female genders are at higher risk of fear of COVID-19 infection ( 18 , 32 , 33 , 35 , 36 , 42 ). The reason for gender-based heterogeneity in contributing fear of COVID-19 can be explained by the prior studies, whereas males were reported as having irresponsible attitudes toward the COVID-19 pandemic, which dramatically decreases their consciousness about the potential infection of the virus ( 43 , 44 ). In addition, studies have reported that women experience more fear and anxiety ( 45 , 46 ); however, they are more resilient and deal well in difficult times ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the present findings, it is evident that female genders are at higher risk of fear of COVID-19 infection ( 18 , 32 , 33 , 35 , 36 , 42 ). The reason for gender-based heterogeneity in contributing fear of COVID-19 can be explained by the prior studies, whereas males were reported as having irresponsible attitudes toward the COVID-19 pandemic, which dramatically decreases their consciousness about the potential infection of the virus ( 43 , 44 ). In addition, studies have reported that women experience more fear and anxiety ( 45 , 46 ); however, they are more resilient and deal well in difficult times ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The online link was circulated by the Exponential Non-Discriminative snowballing method ( 29 , 30 ). An online-based advertisement campaign was designed to recruit participants for this online survey who suffered and eventually recovered from COVID-19 ( 31 ). Participants residing in Bangladesh were randomly selected, and none of them were related to any study.…”
Section: Methodsmentioning
confidence: 99%
“… 22 Being a country of limited resources in the healthcare setting, the authorities imposed a countrywide lockdown to lessen its infection. 22 , 23 During the COVID-19 pandemic, however, students’ psychological health becomes a concern of interest as all the educational institutions were closed down, and their social circle, communication, and interaction processes were also changed. 24 Also, online schooling, the newly introduced method of teaching can be unfavorable for a higher number of students as of difficulties related to understanding materials, technical issues, lack of interest in attending classes, limited access to online schooling materials, and so forth.…”
Section: Introductionmentioning
confidence: 99%